1994
DOI: 10.1007/bf00426182
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of the tibial tray following PCA knee replacement

Abstract: We report two cases in which fracture of the tibial metal tray was thought to be due to improper design of the tray and heavy polyethylene wear. The bone beneath the fractured portion of the tray was deficient and had been replaced by granulomatous fibrous tissue including numerous polyethylene wear particles and foreign-body giant cells. Osteolysis occurred as a tissue reaction to these particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Scott et al (4) postulated that the varus implantation of the tibial component of a total knee arthroplasty increases the concentration of loads with their asymmetric distribution, and can cause a metal fatigue fracture. Also the implantation of the tibial component in external rotation was identified as responsible for excessive loads in tibial components, specifically in total condylar III knee (10) arthroplasties, as well as in the polyethylene fitting zone 5 , 11 , 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Scott et al (4) postulated that the varus implantation of the tibial component of a total knee arthroplasty increases the concentration of loads with their asymmetric distribution, and can cause a metal fatigue fracture. Also the implantation of the tibial component in external rotation was identified as responsible for excessive loads in tibial components, specifically in total condylar III knee (10) arthroplasties, as well as in the polyethylene fitting zone 5 , 11 , 12 .…”
Section: Discussionmentioning
confidence: 99%
“…The two implants used in our study were of the same model made in the United States (Howmedica ® ). Flivik et al (10) and Maruyama et al (11) concluded from their studies that inappropriate design was the main factor involved in fracturing of the tibial component. In our study, the prosthesis used was of modern design, and what drew our attention was the similar fracture location in the two implants.…”
Section: Discussionmentioning
confidence: 99%
“…Scott et al (4) postulated that the varus implantation of the tibial component of a total knee arthroplasty increases the concentration of loads with their asymmetric distribution, and can cause a metal fatigue frac- ture. Also the implantation of the tibial component in external rotation was identified as responsible for excessive loads in tibial components, specifically in total condylar III knee (10) arthroplasties, as well as in the polyethylene fitting zone (5,11,12) . The work of Maquet (13) demonstrated that, in the static position, varus knee deformity produces the exponential growth of loads transmitted to the medial tibial plate, not only through the increase of the lever arm but also through the decrease of the load-bearing surface.…”
Section: Discussionmentioning
confidence: 99%